Clinical and laboratory features of patients diagnosed with alpha‐gal syndrome—2010–2019. Issue 2 (14th October 2022) - Binder, Alison M.; Cherry‐Brown, Dena; Biggerstaff, Brad J.; Jones, Emma S.; Amelio, Claire L.; Beard, Charles B.; Petersen, Lyle R.; Kersh, Gilbert J.; Commins, Scott P.; Armstrong, Paige A.
Abstract: Background: Alpha‐gal syndrome (AGS) is an IgE‐mediated allergy to galactose‐alpha‐1, 3‐galactose. Clinical presentation ranges from hives to anaphylaxis; episodes typically occur 2–6 h after exposure to alpha‐gal‐containing products. In the United States, lone star tick bites are associated with the development of AGS. To characterize features of AGS, we evaluated a cohort of patients presenting for care at the University of North Carolina, focusing on symptoms, severity, and identifying features unique to specific alpha‐gal‐containing product exposures. Methods: We performed a chart review and descriptive analysis of 100 randomly selected patients with AGS during 2010–2019. Results: Median age at onset was 53 years, 56% were female, 95% reported White race, 86% reported a history of tick bite, and 75% met the criteria for anaphylaxis based on the involvement of ≥2 organ systems. Those reporting dairy reactions were significantly less likely to report isolated mucocutaneous symptoms (3% vs. 24%; ratio [95% CI]: 0.1 [0.1, 0.3]) than those who tolerated dairy, and were more likely to report gastrointestinal symptoms (79% vs. 59%; ratio [95% CI]: 1.3 [0.7, 2.6]), although this difference was not statistically significant. Dairy‐tolerant patients demonstrated higher alpha‐gal sIgE titers (as a percentage of total IgE) than dairy‐reactive patients (GM 4.1 [95% CI: 2.7, 6.1] vs. GM 2.5 [95% CI: 1.3, 4.8], respectively; ratio −1.6 [95% CI: −1.0, 3.9]). Conclusion: While tick exposure is common in the southern United States, nearly all AGS patients reported a tick bite. Gastrointestinal symptoms were prominent among those reporting reactions to dairy. Anaphylaxis was common, underscoring the severity and need to raise awareness of AGS among patients and providers. Abstract : This report provides a comprehensive description of the epidemiology, clinical presentation, and laboratory testing trends among large cohort of patients diagnosed with alpha‐gal syndrome in the United States. Eighty six percent reported a history of tick bite, and 75% met the criteria for anaphylaxis based on the involvement of more than 2 organ systems. Patients reporting dairy reactions were significantly less likely to report isolated mucocutaneous symptoms (3% vs. 24%) than those who tolerated dairy and were more likely to report gastrointestinal symptoms (79% vs. 59%).Abbreviation: AGS, alpha‐gal syndrome